Antibacterial activity of mixed pineapple peel (Ananas comosus) extract and calcium hydroxide paste against Enterococcus faecalis - Intan Fajrin Arsyada; Devi Rianti; Elly Munadziroh (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2018)
Background: Enterococcus faecalis (E. faecalis) is the bacteria most commonly resulting from failed root canal treatment. Intracanal medicament is used to enhance the success of root canal treatment. A material widely used for this purpose is calcium hydroxide. However, its ineffectiveness in eliminating E. faecalis requires the addition of other antibacterial substances, such as iodoform which has the disadvantage of having toxic effects on tissues. Pineapple peel has antibacterial properties because it contains chemical compounds, such as flavonoid, saponin, tannin, as well as the enzyme bromelain. Purpose: The aim of the study was to determine the antibacterial activity of a mixture of pineapple peel extract at 6.25% and 12.5% concentrations and calcium hydroxide paste at a ratio of 1:1 compared to100% calcium hydroxide and a mixture of calcium hydroxide and iodoform paste against E. faecalis. Methods: The research was laboratory-based experiment in nature. Sample groups were divided into two control groups (one featuring100% calcium hydroxide paste and a second featuring a mixture of calcium hydroxide and iodoform paste) and two treatment groups (mixture of pineapple peel extract and calcium hydroxide paste in 6.25% and 12.5% concentrations with ratio 1:1). The method was using agar diffusion. The result data were analyzed by One Way Anova test. Results: The highest average of the inhibitory zone occurred in group with a mixture of pineapple peel extract 12.5% and calcium hydroxide paste while the smallest average was that of group with a mixture of calcium hydroxide and iodoform paste. Conclusion: Mixture of pineapple peel extract in 6.25% and 12.5% concentrations and calcium hydroxide paste ratio 1:1 has higher antibacterial activity than paste of 100% calcium hydroxide and mixture of calcium hydroxide and iodoform paste againts E. faecalis.